Determining if honey bees (Apis mellifera) collect pollen from anemophilous plants in the UK. (3rd April 2023) - Pound, Matthew J.; Vinkenoog, Rinke; Hornby, Sarah; Benn, Jonty; Goldberg, Shannon; Keating, Barbara; Woollard, Flora
Abstract: Whether insect pollinators use wind-pollinated plants have implications for insect monitoring and conservation strategies in a wide range of environments. Habitats, such as coniferous plantations and arable crops of the Poaceae family are not typically considered priority for the monitoring of insect pollinators or habitat enhancement. Further many pollinator monitoring techniques focus on flowers and do not count insect interactions with wind-pollinated plants. Using two honey bee colonies from distinct environments (urban and rural) in north east England, we investigate the use of wind-pollinated plants over the summer of 2021. We combine honey bee pollen pellet analysis with airborne pollen sampling to investigate whether honey bees use three common wind-pollinated plant groups ( Pinus sp., Plantago sp. and Poaceae) that have previously been considered sources of forage. Our results show that honey bees do forage on Plantago and Poaceae pollen, in line with previous studies. However, we show statistically that Pinus pollen is contamination from the atmosphere and not actively collected. It is important to consider airborne contamination before making interpretations based on small amounts of pollen in samples of bee products. The use of members of the Poaceae has implications for insect pollinator monitoring in urban environments, which has not always been considered in past studies.